Chiral rhodium(iii)–azobenzene complexes as photoswitchable DNA molecular locks. Issue 27 (11th March 2022) - Lin, Mingwei; Zou, Shanshan; Li, Tingzhen; Karges, Johannes; Chen, Yu; Zhao, Yukun; Ji, Liangnian; Chao, Hui
Abstract : Two chiral rhodium(iii ) complexes with an azobenzene moiety were developed to act as photoswitchable DNA molecular locks, which can photo-regulate DNA transcription in vitro . Abstract : Chiral rhodium(iii )–azobenzene complexes that are able to intercalate into DNA were developed. Upon light exposure, the azobenzene moiety of the metal complexes can photoisomerize from the trans -form to the cis -form, and strongly stabilize the DNA double-helix and modulate DNA transcription. This study presents the first example of metal-based photoswitchable DNA molecular locks.